2005
DOI: 10.1038/modpathol.3800352
|View full text |Cite
|
Sign up to set email alerts
|

Lack of association of cytomegalovirus with human brain tumors

Abstract: Cytomegalovirus (CMV) is thought to possess oncogenic properties and has been linked with a number of human malignancies. CMV infection was recently described in association with malignant gliomas. The intent of the present study was to further investigate the reported association between CMV and malignant gliomas. Tissue from 22 brain tumors of various histologic types and grades, four normal brains, six breast carcinomas, six colon carcinomas, six lung carcinomas, and six sarcomas were evaluated for the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
82
2
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(93 citation statements)
references
References 40 publications
4
82
2
3
Order By: Relevance
“…The data suggest that HCMV proteins may have a role in genesis of glioblastoma and immunotherapy studies for glioblastoma targeting viral proteins have been attempted in several laboratories. However, Lau et al 5 did not detect any association between HCMV and glioblastomas by conventional PCR and other methods, and another group reported no involvement 6 after analyzing a large number of samples. The role of methodology may be important and Cobbs et al 1 observed that almost all primary tumor specimens from patients with glioblastoma multiforme expressed HCMV immediate early (IE) proteins, whereas adjacent normal cells did not.…”
mentioning
confidence: 99%
“…The data suggest that HCMV proteins may have a role in genesis of glioblastoma and immunotherapy studies for glioblastoma targeting viral proteins have been attempted in several laboratories. However, Lau et al 5 did not detect any association between HCMV and glioblastomas by conventional PCR and other methods, and another group reported no involvement 6 after analyzing a large number of samples. The role of methodology may be important and Cobbs et al 1 observed that almost all primary tumor specimens from patients with glioblastoma multiforme expressed HCMV immediate early (IE) proteins, whereas adjacent normal cells did not.…”
mentioning
confidence: 99%
“…This result suggested that none of the CNS tumours contained HCMV genomes and/or proteins in a significant proportion of tumour cells. In another work, Lau et al (2005) investigated HCMV in a group of 22 brain tumours of various histological types and grades (8 GBMs, 6 grade III astrocytomas, 3 grade II astrocytomas, 2 oligodendrogliomas and 3 ependymomas) and controls (4 normal brain tissue samples and other tumours) by PCR, ISH with a probe complementary to HCMV early gene mRNA and IMH. None of the brain tumours or normal brain tissue tested demonstrated the expression of the HCMV proteins pp65 or p52 by IMH.…”
mentioning
confidence: 99%
“…In the ensuing years, the debate has been well-joined (see e.g. [81][82][83][84][85]). mCMV-induced, oncocytic-like, metaplasia and atypical ductal epithelial hyperplasia in embryonic SMGs suggest that the relationship between CMV and salivary gland tumors deserves a fresh look, particularly since salivary glands are a primary target for productive infection, subsequent latency, and reactivation.…”
Section: --mentioning
confidence: 99%